A Picture is Worth 1,000 Words - Ai, Angela C; Maloney, Francine L; Hickman, Thu-Trang; Wilcox, Allison R; Ramelson, Harley; Wright, Adam (Applied Clinical Informatics, 2017)
Objective: To understand how clinicians utilize image uploading tools in a home grown electronic health records (EHR) system.Methods: A content analysis of patient notes containing non-radiological images from the EHR was conducted. Images from 4,000 random notes from July 1, 2009 – June 30, 2010 were reviewed and manually coded. Codes were assigned to four properties of the image: (1) image type, (2) role of image uploader (e.g. MD, NP, PA, RN), (3) practice type (e.g. internal medicine, dermatology, ophthalmology), and (4) image subject.Results: 3,815 images from image-containing notes stored in the EHR were reviewed and manually coded. Of those images, 32.8% were clinical and 66.2% were non-clinical. The most common types of the clinical images were photographs (38.0%), diagrams (19.1%), and scanned documents (14.4%). MDs uploaded 67.9% of clinical images, followed by RNs with 10.2%, and genetic counselors with 6.8%. Dermatology (34.9%), ophthalmology (16.1%), and general surgery (10.8%) uploaded the most clinical images. The content of clinical images referencing body parts varied, with 49.8% of those images focusing on the head and neck region, 15.3% focusing on the thorax, and 13.8% focusing on the lower extremities.Conclusion: The diversity of image types, content, and uploaders within a home grown EHR system reflected the versatility and importance of the image uploading tool. Understanding how users utilize image uploading tools in a clinical setting highlights important considerations for designing better EHR tools and the importance of interoperability between EHR systems and other health technology.Citation: AC Ai, FL Maloney, T-T Hickman, AR Wilcox, H Ramelson, A Wright. A picture is worth 1,000 words: The use of clinical images in electronic medical records. Appl Clin Inform 2017; 8: 710–718 https://doi.org/10.4338/ACI-2016-10-RA-0180
Keywords: Electronic health records; clinical images